(untitled) (Development Service Industry Management, 2024)
The composition of business processes that are appropriate to implement the system of HR-engineering in a modern enterprise. The main tasks, principles and stages of HR-engineering implementation at the enterprise are considered. Detailed description of the complex of works in the practical application of the principles of engineering business process in the enterprise. The positive and negative consequences of the introduction of the method of engineering business processes. HR-engineering is implemented at all levels of business process management and isdeveloped in different ways of changing the business environment. HR-engineering techniques include the latest tools, advanced technologies and tools for the transformation of HR-processes and their optimization using digitalization. The study systematizes the latest technologies and tools of HR management and describes their integrated application in HR-engineering technology. A conceptual scheme for understanding HRprocesses as an important component of business processes of the enterprise is proposed. The article examines the use of modern HR technologies in enterprise management. Social challenges and modern business priorities regarding the transformation of HR processes have been studied. The global trends of the innovative development vector of digitalization of HR of the organization have been determined. The essence of the reengineering process was formed as a direction of improving business processes in the organization’s HR engineering system. The stages of the introduction of HR engineering as an innovative vector of the development of the organization’s business economy have been constructed. The map of the restructuring of the business process "forming the personnel potential of the enterprise" on the basis of reengineering is substantiated. The main means of HR engineering, which are used during the design and optimization of HR processes, are given. The positive consequences of the practical application of the HR-engineering method of business processes at the enterprise are characterized.